A representação do brasileiro na ficção de Eça de Queiroz : O Primo Basílio e a correspondência de Fradique Mendes - Costa, Luciana Rosa (2021)
In this work, we investigate the representation of the “Brazilian people” in the novels O Primo Basílio (“Cousin Bazilio”) (1878) and Correspondência de Fradique Mendes (“Correspondence of Fradique Mendes”) (1900), both by Eça de Queiroz, in order to identify how the Portuguese writer approached the image of Brazil and Brazilians in these works. The methodology of this research consists of developing a theoretical and critical approach on how the characters of Bazilio and Fradique are presented in these two works, regarding the relations of identity between Portugal and Brazil at the end of the 19th century. The topics raised in the analysis discuss issues as identity, otherness and stereotypes. For the analysis, we are guided by the thoughts of authors such as Homi Bhabha (1998) and Julia Kristeva (1994), while seeking to weave discussions about stereotypes and the relationships of otherness. To these considerations, we add an approach on stigmas, present in the texts of Erwing Goffman (1981). The relations between Portugal and Brazil, in the context of the emigration movements that took place at the end of the 19th century, are grounded on the studies of authors such as Boris Fausto (2015), Lilia Schwarcz (2015) and Paulo Ricardo Kralik Angelini (2016). We also utilize as a support the ideas of multiculturalism and representation, present in the works of Silvia Scott (2012) and Robert Stam (2008), intending to make a parallel with the reflections around the Queiroz’s fiction, based on the thoughts of Carlos Reis (2011) and Eduardo Lourenço (1982, 2004). In the novel “Cousin Bazilio”, we give emphasis to the characters Bazilio and Jorge, putting them in contrast with each other, in order to lecture about the Portuguese emigration theme. In the “Correspondence of Fradique Mendes”, we try to highlight a new perspective from Eça regarding the issues discussed in the first novel, but with the same critical style built from social aspects. We observed, through the analyzes herein that Eça goes through what we call in this research as two moments in relation to Brazil in his literary life, both with its distinctions from one another. It was verified that in the “Cousin Bazilio” novel, the representation of the Brazilian is marked by the caustic and ironic tone and also by its ambiguity. In the “Correspondence of Fradique Mendes”, however, we observe that the author starts to distinguish the born Brazilian from the Portuguese emigrant who returns to Portugal. We conclude that this reflection by the author is due to the need of Portugal and Brazil to be defined as an authentically identity. In addition, we also complement the conclusion that Eça de Queiroz was a writer ahead of his time, who, even though was influenced by the fervor of the moment and the literary changes of his time, proposes, by the use of the characters from his book, a deep reflection on the contradictions existing in Portuguese and Brazilian societies, placing in the context of representations of the "other" a criticism of the very vices that existed in Portugal.